Detection of Human Papilloma Virus in Oral Potentially Malignant Disorders and Oral Squamous Cell Carcinoma - Ghosh, Snehashish; Wazir, Sartaj Singh; Shah, Rajesh; Upadhyay, Manoj Kumar; Gupta, Rahul; Singh, Harendra Mohan (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Human Papilloma Virus 16 and 18 affects the keratinocytes of oral mucosa and skin and can lead to the development of dysplastic lesions and ultimately into invasive oral squamous cell carcinoma. The objective of the present study was to evaluate the presence of human Papilloma virus 16 and 18 DNA in already diagnosed oral potentially malignant disorders and oral squamous cell carcinoma. Methods: 200 biopsy specimens (50 each) of already diagnosed leukoplakia, oral lichen planus (OLP), oral submucous fibrosis (OSMF) and oral squamous cell carcinoma was included for the study. A total 50 control tissue sections, which were obtained during removal of impacted teeth were also included in the study. All 250 specimens were subjected to polymerase chain reaction (PCR) for the identification of HPV 16 and 18. The results are analyzed using Statistical Package of Social Sciences (SPSS) version 16 software and Pearson’s chi square test was used for statistical analysis. Results: HPV 16 and 18 was noted in all the OPMDS and oral cancer specimens but the results were not statistically significant. However, not even a single case of control tissue showed the presence of HPV 16 and 18. Conclusions: The results of the present study shows HPV 16 and 18 is present in oral cancer as well as OPMDS, therefore it could be implicated in the pathogenesis of the above mentioned conditions.